As relações raciais no discurso jornalístico: uma análise a partir das categorias de subentendido e silenciamento - Ferraz, Nayara Dias (2021)
This dissertation is based on studies of race relations and seeks to understand how they are constructed within newspapers. For such, we chose Whiteness and Discourse Analysis as the bases for the development of this study. In order to understand this construction, we used the contribution of the discourse of whiteness, which is constituted from the moment when we verify the ideology based on the power of white identity in the discourse of subjects. For the development of this work, we formulated the following questions: how are racial relations built within the journalistic discourse? How does the discourse of whiteness present itself in the journalistic discourse? In order to answer these questions, our general objective was to verify the construction of race relations within the journalistic discourse and, as specific objective, to identify how race relations are built within the journalistic discourse, based on the categories of implicitness and silencing and verify how the discourse of whiteness is structured and characterized within the journalistic discursive field. We carried out a qualitative research and used Discourse Analysis, both for the construction of the theory and as a contribution to the analysis of the corpus. Besides, we chose the implied and the silencing as categories of analysis. We used the Folha de S. Paulo newspaper, published from January to July 2020, using racism as a research filter, to compose the corpus. Conceptualizations about Discourse Analysis, the characteristics of journalistic discourse, racism and whiteness are addressed to establish the theoretical framework. The following results were found in the analysis: it is possible to identify the presence of the discourse of whiteness in the journalistic field, but in a very subtle way. Within the journalistic discourse, the discussion about the discourse of whiteness is silenced or modalized by the enunciators. Regarding the discursive place, the discourse of whiteness is latent in society, circulates freely through it, and can be present in both white and black subjects. The discussion about white privilege and its implications for racial relations within society circulates atopically through society and the news.